Fungsi Manajemen Pengawasan, Tahapan dan Kerangka Manajemen Pengawasan Dalam Perspektif Hadis - Lyindira Putri; Padlianor; Suraijiah (PT. Hasba Edukasi Mandiri, 2025)
This study examines management supervision from an Islamic perspective, focusing on its functions, stages, and framework based on hadis. Supervision is essential for ensuring organizational goals are met and activities are properly implemented, particularly in Islamic education. Key principles such as trustworthiness (amanah) and Allah’s omnipresence underpin supervision in Islam, emphasizing moral and spiritual accountability. Supervision is divided into internal (based on faith and tawhid) and external (mutual advice and social oversight). The stages include setting standards, measuring performance, and continuous evaluation for improvement. Hadis highlights that supervision must be carried out with integrity, faith, and awareness of Allah’s watchfulness. The findings underscore that Islamic supervision integrates moral, spiritual, and administrative elements, fostering responsible management rooted in Islamic values, thereby strengthening organizational effectiveness and sustainability